Evolution of plant conducting cells perspectives from key regulators of vascular cell differentiation - Ohtani, Misato (Journal of experimental botany, 2017)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.